Surgical outcome of management of perforated peptic ulcer (Al-Gumhori General Hospital, Sana-Yemen, From January 2017 to January 2020) - Abdulwally, Abdullah Mohammed; Thabet, Yasser Abdurabo; Albadani, Moahmmed Noman; Alamri, Ali Lotf (Journal of medical and pharmaceutical sciences, 2021)
Background: Perforated peptic ulcer (PPU) is a common life-threatening surgical emergency. The discovery of H. pylori (1985) changed the concept of the management of peptic ulcer. Nowadays reduction in gastric acid production with proton pump inhibitors along with eradication of H. pylori is recommended. Objective: to analysis the surgical outcome for management of perforated peptic ulcer in Al-gomhuri Hospital during 2017-2020. Methods: Clinically suspected cases of PPU were confirmed by radiological and laboratory investigation. These patients were subjected to exploratory laparotomy with Graham’s omental patch repair after adequate fluid resuscitation with optimal hemodynamic status with peritoneal drainage Postoperatively these patients kept in SICU and closely monitored. Data were collected, tabulated and analyzed. Results: 62 cases enrolled; Male patients were predominant than female in a ratio of 60:2. Age ranges from 20 to >60 years. Majority of the patients belongs to the age group 30-40 years of age. The morbidity and mortality rates were (20%) and (3.2%) respectively. Conclusions: Adequate fluid resuscitation with optimal hemodynamic status and optimal kidney function is the key to decrease morbidity and mortality rates. Simple closure with omental patch followed by H. pylori eradication is effective with an excellent outcome in most of survivor despite late presentation. Definitive surgery for ulcer recurrence is no more done except in special situations.